Implementasi Cluster Message Broker Sebagai Solusi Skalabilitas Middleware Berbasis Arsitektur Publish-Subscribe pada Internet of Things (IoT) - Jessy Ratna Wulandari; Eko Sakti Pramukantoro; Heru Nurwasito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
IoT middleware that used to solve syntactical interoperability, face a limited storage resource due toRedis implementation which used RAM as a data buffer. This problem can be solved by adding a clustermessage broker to distributing data to several Redis. The goal of this research is to develop a clustermessage broker from several Redis that already configured into cluster mode, in order to randomlydistribute data or topic into several Redis. Besides that, Ioredis also added the middleware to integratecluster with the middleware. Testing was done to test the capability of the sensor node as a publisher,cluster message broker in the middleware, and subscriber also to test the distributed data or topic inseveral Redis. The results show that data sent from the publisher can be received by middleware andmiddleware can send data from the publisher to the subscriber. Besides that, data or topic received bymiddleware can be distributed to the several Redis in the cluster.